Epidemiology and Diagnosis of Helicobacter pylori infection. (15th September 2015) - Mentis, Andreas; Lehours, Philippe; Mégraud, Francis
Abstract: During the period reviewed, prevalence studies were essentially performed in less economically advanced countries and a high prevalence was found. The traditional risk factors for Helicobacter pylori positivity were mostly found. Transmission studied by molecular typing showed a familial transmission. The eventual role of water transmission was explored in several studies with controversial results. Concerning diagnosis, most of the invasive and noninvasive methods used for the diagnosis of H. pylori infection are long standing with efficient performance. The most interesting recent improvements in H. pylori diagnosis include advances in endoscopy, developments in molecular methods, and the introduction of omics‐based techniques. Interpretation of old or newer method should take into account the pretest probability and the prevalence of H. pylori in the population under investigation.